Frog in the Pan: Continuous Information and Momentum - Gurun, Umit (Institutional Knowledge at Singapore Management University, 2010)
We develop and test a frog-in-the-pan hypothesis that predicts investors are less attentive to information that arrives continuously in small amounts than to information with the same cumulative stock price implications that arrives in large amounts at discrete timepoints. Intuitively, we hypothesize that a series of gradual frequent changes attracts less attention than infrequent dramatic changes. Consistent with our frog-in-the-pan hypothesis, we find strong evidence that continuous information induces stronger return continuation. Over a six-month holding period, momentum decreases monotonically from 8.86% for stocks with continuous information during their formation period to 2.91% for stocks with discrete information. Higher media coverage and higher analyst coverage are associated with more discrete and more continuous information, respectively.